A gene recombination method for machine tools design based on complex network. Issue 5 (March 2016) - Zhao, Liping; Diao, Guangzhou; Yan, Peng; Yao, Yiyong; Chen, Hongren
Abstract Aiming at the diversity and complexity of machine tools design, a novel gene recombination method based on complex network is proposed in this paper. The contribution of proposed method is to extract the assembly components of machine tools as the structure genes for defining the extraction rules of network elements (node, edge, weight). Then, a machine tools design network (MTDN) model is built to describe the complex relationships between the structure genes. Furthermore, some indices are defined and calculated to evaluate the MTDN performance which is used to recombine the structure genes and enumerate the possible design schemes of machine tools structure. The self-organization interoperability of MTDN is discussed to select the optimal schemes of machine tools design. Finally, a case about machine tools design of globoidal cams is presented to validate the proposed method. It is expected that the proposed method can provide the support for machine tools design in manufacturing fields.